P.038 Impact of Disease Severity on Presentation Subtype and OnabotulinumtoxinA Utilization in Patients with Cervical Dystonia in the CD PROBE Completer Population. (November 2021) - Agarwal, P; Barbano, R; Moore, H; Schwartz, M; Zuzek, A; Patel, A
Abstract : Background: The impact of cervical dystonia (CD) severity on presentation subtype and onabotulinumtoxinA utilization was examined in the completer population from CD PROBE (CD Patient Registry for Observation of BOTOX ® Efficacy). Methods: In this multicenter, prospective, observational registry, patients with CD were treated with onabotulinumtoxinA according to injectors' standard of care. Completers were patients that completed all 3 treatment sessions and had accompanying data. Results: Of N=1046 patients enrolled, n=350 were completers. Completers were on average 57.3 years old, 74.9% female, 94.6% white, and 60.6% toxin-naïve. Baseline severity was mild in 32.6%, moderate in 54.3%, and severe in 13.1%. Torticollis was the most common presentation at baseline (mild: 44.7%, moderate: 55.8%, severe: 63.0%), followed by laterocollis (mild: 42.1%, moderate: 32.6%, severe: 26.1%). Median onabotulinumtoxinA dose increased over time; 160U–200U for torticollis and 170U–200U for laterocollis. For all severities, median total dose increased from injection 1 to injection 3 (mild: 138U–165U, moderate: 183U–200U, severe: 200U–285U). Eighty-one patients (23.1%) reported 139 treatment-related adverse events. There were no treatment-related serious adverse eventsand no new safety signals. Conclusions: CD severity impacted presentation subtype frequency and onabotulinumtoxinA utilization in CD PROBE, with higher and tailored dosing observed over time and with increasing disease severity.